2003
DOI: 10.1002/ejoc.200300213
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structural Characterization of PNA‐DNA Quadruplex‐Forming Chimeras

Abstract: The synthesis and structural characterization of four PNA‐DNA chimeras − 5′TGGG3′‐t (C1), 5′TGG3′‐gt (C2), t‐5′GGGT3′ (C3) and tg‐5′GGT3′ (C4), where lower and upper case letters indicate PNA and DNA residues, respectively − are reported. The oligomers were synthesized through the use of commercially available Bhoc/Fmoc PNA monomers and 3′‐ or 5′‐phosphoramidite nucleosides as building blocks. All the molecules were studied by 1H NMR, CD and UV spectroscopy and by molecular modelling. The CD spectra and NMR sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Recently, PNA-DNA G-rich strands were found to assemble to form quadruplex structures [116]. The ability of PNA-DNA chimeras to form quadruplexes is important because a PNA tract should enhance the stability against degradation by exonucleases, and hence the biological activity of these structures involved as active aptamers in a number of quadruplex-binding proteins [117].…”
Section: Modified Aptamersmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, PNA-DNA G-rich strands were found to assemble to form quadruplex structures [116]. The ability of PNA-DNA chimeras to form quadruplexes is important because a PNA tract should enhance the stability against degradation by exonucleases, and hence the biological activity of these structures involved as active aptamers in a number of quadruplex-binding proteins [117].…”
Section: Modified Aptamersmentioning
confidence: 99%
“…The A most radical modification to the natural structure of DNA, recently applied to quadruplex forming oligonucleotides, is the introduction of peptide nucleic acid (PNA) units into the nucleic acid backbone carrying to PNA -DNA chimeras. We demonstrated that d(tGGGT) and d(TGGGt) chimeric sequences (the small letters indicate PNA units) are able to form quadruplexes of comparable stability with respect to the reference quadruplex [d(TGGGT)] 4 [116]. A more detailed thermodynamic study was carried out in our laboratory (paper in preparation) on the chimeric sequences d(tGGGGT) and d(TGGGGt), where the thymine residues were alternatively substituted with a PNA unit at the 3' or the 5' end of the sequence.…”
Section: Thermodynamics Of Modified Quadruplexesmentioning
confidence: 99%
“…Indeed, the incorporation of a modified nucleotides into the oligonucleotide may produce useful change in physical and biological properties of the resulting DNA fragments, due to an increased stability, or higher resistance to nucleolytic enzymes 15. Different modifications have been proposed involving the base, the phosphate group or the sugar‐phosphate backbone in an attempt to stabilize quadruplex structure 16–21. For example, it was demonstrated that a nucleic acids analogs such as peptidic nucleic acids (PNAs) can form PNA/DNA hybrid quadruplexes 19.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that PNA-DNA chimeric strands are able to form quadruple structures with higher thermodynamic stability in comparison with the unmodified strands. 18,20 Another promising class of nucleic acid analogs is that of locked nucleic acid (LNA) (Figure 1). In the LNA monomers the furanose ring is locked with a 2 0 -O,4…”
Section: Introductionmentioning
confidence: 99%